2017
DOI: 10.1177/0898264317690866
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Lipoproteins, Disability, and Physical Function Among Older Costa Rican Adults

Abstract: Lower levels of lipoproteins may suggest worse physical function, but the association may differ by sex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Despite the lack of consensus in associations between biomarkers and frailty in previous studies [ 11 ], a moderate link between haemoglobin and frailty [ 26 ] was reported, while there was a reported link between low HDL level and ADL-related disability [ 27 ]. Supporting our hypothesis, the associations between these markers and the physical aspect of frailty extend additional support to these existing findings.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of consensus in associations between biomarkers and frailty in previous studies [ 11 ], a moderate link between haemoglobin and frailty [ 26 ] was reported, while there was a reported link between low HDL level and ADL-related disability [ 27 ]. Supporting our hypothesis, the associations between these markers and the physical aspect of frailty extend additional support to these existing findings.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the physiological function of HDL-C, HDL-C is regarded as a positive factor of health in the whole population. Relevant research demonstrates that the higher the level of HDL-C, the better the functional status, 29 ADL, 30 and cognitive function 14 of the elderly. This study found that the increase of HDL-C in centenarians had the strongest protective effect on ADL disability, suggesting that the prevention of hypoHDL-C in the elderly and centenarians has important health significance.…”
Section: Discussionmentioning
confidence: 99%